2022
DOI: 10.1038/s41598-022-12979-8
|View full text |Cite
|
Sign up to set email alerts
|

The importance of extrinsic and intrinsic compensatory mechanisms to body posture of competitive athletes a systematic review and meta-analysis

Abstract: The aim of this systematic review (qualitative analysis) was to identify the variables of changes induced by extrinsic (sport specific training) and intrinsic (individual anatomical predispositions) compensatory mechanisms that impact on the physiological magnitude of spinal curvatures in the sagittal plane and their deviations in the frontal plane. Furthermore, the aim of the quantitative analysis was to verify and objectivize the impact of these variables on athlete’s body posture. A search of electronic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
2
9
0
1
Order By: Relevance
“…This is in agreement with our previous research [15] that suggested both intrinsic and extrinsic compensatory mechanisms as the main factors affecting body posture and inducing musculoskeletal pain in Para athletes. Similar relationships were confirmed in able-bodied athletes by a meta-analysis conducted by Zwierzchowska et al [31] Considering the issue of body's external compensatory mechanisms our study did not find significant relationships between NMQ-7 and sport-specific training. However, the results indicate that the location of musculoskeletal complaints is associated with the sport practiced.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in agreement with our previous research [15] that suggested both intrinsic and extrinsic compensatory mechanisms as the main factors affecting body posture and inducing musculoskeletal pain in Para athletes. Similar relationships were confirmed in able-bodied athletes by a meta-analysis conducted by Zwierzchowska et al [31] Considering the issue of body's external compensatory mechanisms our study did not find significant relationships between NMQ-7 and sport-specific training. However, the results indicate that the location of musculoskeletal complaints is associated with the sport practiced.…”
Section: Discussionsupporting
confidence: 88%
“…This is in agreement with our previous research [ 15 ] that suggested both intrinsic and extrinsic compensatory mechanisms as the main factors affecting body posture and inducing musculoskeletal pain in Para athletes. Similar relationships were confirmed in able-bodied athletes by a meta-analysis conducted by Zwierzchowska et al [ 31 ]…”
Section: Discussionsupporting
confidence: 74%
“…Each task is scored according to ability, with a maximum score of 3 indicating good task performance (21 points indicates a full score) [7] .The FMS has a good effect on improving athletes' own de ciencies and di cult technical movements, and has the effect of screening for injury risk [8] .Functional training with the FMS has been shown to be effective in improving athletes' balance, injury prevention, stability and improving athletic performance [9,10,11] . To improve FMS scores, training systems such as no-load training, kettlebells, core boards and cable machines, training forms such as TRX, Omnia, CrossFit and BOSU are recommended to develop muscular strength, bilateral symmetry, trunk stability and sports FMS scores [12,13] .Several studies have shown that functional training has a signi cant effect on core stability and movement balance [14] , and that professional athletes in particular tend to have postural de cits or spinal curvature de cits in the sagittal and frontal planes [15] , and therefore in competition, As athletes often suffer from potential functional impairments that affect the perfect performance of di cult movements and movement techniques [16] , that only physically t athletes can perform combinations of high technical speci cations and standards and achieve excellent results [17] , and functional movement screening can accurately assess the functional de ciencies of athletes in the process of exercise and develop training program that match the characteristics of the body and specialty to compensate for the de ciencies in their own qualities. The body trunk position in the limbs of the core connection, a speci c and detailed core stability training plays a signi cant role in improving balance and postural stability [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Even though karate is a symmetrical and complex sport [ 9 ], the specificity of kata performance includes also asymmetric movement patterns. Therefore, elite-level athletes may show disturbances both in the muscular and skeletal systems as a consequence of adaptive and thereafter compensatory changes induced by multiple repetitions of the same sport-specific movements (external compensation) [ 14 ]. Furthermore, when the basic mechanisms responsible for the musculoskeletal function are disturbed, karatekas are also likely to be predisposed to compensatory and thereafter adaptive changes in the biomechanical structures, which are known as internal compensation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%